Complete Genome Sequences of Two Strains of the Meat Spoilage Bacterium Brochothrix thermosphacta Isolated from Ground Chicken - Paoli, George C. (Genome Announc, 2017)
Brochothrix thermosphacta is an important meat spoilage bacterium. Here we report the genome sequences of two strains of B. thermosphacta isolated from ground chicken. The genome sequences were determined using long-read PacBio single-molecule real-time (SMRT) technology and are the first complete genome sequences reported for B. thermosphacta.